Immunity: the importance of adequate nutrition in times of pandemic (Research, Society and Development, 2021)
The act of eating is a necessary practice for our existence. Healthy eating is an important tool for human health and quality of life. Thus, the aim of the present study was to expose the importance of adequate nutrition in the immune response in times of pandemic. To this end, a descriptive literature review with a qualitative approach was carried out, which selected articles that addressed the theme in a time frame between 2012 and 2021. The pandemic scenario generated by COVID-19 reinforced the need for public policies that minimize the food and nutritional insecurity of marginalized families. Since, even with legislation in Brazil that guarantees the right to healthy food, as a result of the economic crisis resulting from the isolation and unemployment measures, there has been a direct impact on the worsening of the poverty situation. It is known that foods provide us with essential nutrients for strengthening the immune system, among these studies they mention: Vitamin A, Vitamin C, Vitamin D, Vitamin E, Zinc, Selenium, Iron and Magnesium. Therefore, in times of pandemic eating healthy is essential. In this sense, the choice of ingested foods should prioritize the nutrients present in the food.